Aprendendo com a ciência cognitiva da leitura: um estudo de caso de intervenção fônica na alfabetização - Paolucci, Karina (2023)
Mastering written language is fundamental to the effective exercise of citizenship. It is a complex skill, as it involves different cognitive and linguistic functions such as memory, attention, reasoning, and comprehension. Due to its importance as a means of developing human intelligence, the Cognitive Science of Reading emerged, based on the union of other sciences: Cognitive Neuroscience, Cognitive Psychology, and Cognitive Linguistics. These three sciences observe and study the human mind in relation to brain functioning. Studies concerning Cognitive Neuroscience show that reading needs to be taught. Learning is possible through neuronal recycling owing to the plasticity of the nervous system. Thus, it is possible to think that every human being is capable of learning. Therefore, the objective of this research was to analyze the literacy process through phonics instruction applied to a 5th grader in elementary school diagnosed with Autism Spectrum Disorder, Attention-Deficit Hyperactivity Disorder, Language Disorder, and Speech Disorder. Initially, activities to develop executive functions, object and time organization, body and sound awareness, autonomy, and group belonging were performed. After 6 months of intervention, I started the activities based on phonics instruction, teaching the association of letters with their sound, that is, the explicit teaching of the grapheme-phoneme relationship. This important period lasted from February to October 2022. In this dissertation, the period from August to October will be described in its process and product dimensions: the participant showed improvements in organization, attention, memory, autonomy, confidence, gross and fine motor coordination, communication, and group belonging. Initially the student had few words in her pictorial language repertoire. At the end of these three months of intervention, a transition from the pre-alphabetic phase to partial alphabetic was observed, with the reading of trisyllabic words of single syllables. This result showed that the intervention with phonics instruction was effective in this case of Neurodevelopmental Disorder